2007
DOI: 10.1111/j.1745-6584.2007.00388.x
|View full text |Cite
|
Sign up to set email alerts
|

Hydraulic Tomography for Detecting Fracture Zone Connectivity

Abstract: Fracture zones and their connectivity in geologic media are of great importance to ground water resources management as well as ground water contamination prevention and remediation. In this paper, we applied a recently developed hydraulic tomography (HT) technique and an analysis algorithm (sequential successive linear estimator) to synthetic fractured media. The application aims to explore the potential utility of the technique and the algorithm for characterizing fracture zone distribution and their connect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
66
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 85 publications
(67 citation statements)
references
References 66 publications
(82 reference statements)
1
66
0
Order By: Relevance
“…These tests are useful but not flawless (Wu et al, 2005) because they depend on strong assumptions such as Theis' homogeneous aquifer assumption (Fetter, 2001). Pumping tests evolved into hydraulic tomography which allows obtaining high resolution images of the hydraulic conductivity distribution (Yeh and Liu, 2000;Liu et al, 2002;Zhu and Yeh, 2005;Illman and Tartakovsky, 2006;Zhu and Yeh, 2006;Hao et al, 2008;Illman et al, 2008;Yin and Illman, 2009). However, this method requires several wells and prior knowledge about the location of fractures.…”
Section: Introductionmentioning
confidence: 99%
“…These tests are useful but not flawless (Wu et al, 2005) because they depend on strong assumptions such as Theis' homogeneous aquifer assumption (Fetter, 2001). Pumping tests evolved into hydraulic tomography which allows obtaining high resolution images of the hydraulic conductivity distribution (Yeh and Liu, 2000;Liu et al, 2002;Zhu and Yeh, 2005;Illman and Tartakovsky, 2006;Zhu and Yeh, 2006;Hao et al, 2008;Illman et al, 2008;Yin and Illman, 2009). However, this method requires several wells and prior knowledge about the location of fractures.…”
Section: Introductionmentioning
confidence: 99%
“…Solving Eq. (27) gives both the minimum travel time from a point x to its nearest known neighbor x k , tĂ°xÞ and the nearest neighbor interpolant of this point pĂ°xÞ which has the value f k (corresponding to x k ). The metric tensor field DĂ°xÞ derived from the guiding image allows computing the nearest neighbor interpolant pĂ°xÞ.…”
Section: Image-guided Interpolationmentioning
confidence: 99%
“…Over the past two decades, several numerical and field studies have demonstrated how steadystate hydraulic tests can be used to image hydraulic conductivity or transmissivity (e.g., [12,21,40,59]). Transient pumping tests can also be used to estimate both of the specific storage and hydraulic conductivity fields (e.g., [3,27,64]). Hydraulic conductivity tomography can also be combined with the temporal moments method to reconstruct the hydraulic parameters heterogeneities (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Day-Lewis et al (2006) interpret field experimental cross-hole radar, tracer, and hydraulic data at a fractured rock aquifer at the same site and found that combining time-lapse geophysical monitoring with conventional hydrologic measurements improved the characterization of a fractured rock aquifer. Recent advances in the characterization of spatially distributed hydraulic properties of heterogeneous aquifers using hydraulic tomography (McDermott et al 2003;Brauchler et al 2003;Zhu and Yeh 2006;Hao et al 2008) provide a potential solution to this difficult problem.…”
Section: Introductionmentioning
confidence: 99%